1983
DOI: 10.1113/jphysiol.1983.sp014954
|View full text |Cite
|
Sign up to set email alerts
|

Reflex responses at the human ankle: the importance of tendon compliance.

Abstract: SUMMARY1. Subjects with active stretch reflexes responded to an imposed sinusoidal movement of the ankle joint with a reflex force whose amplitude and timing varied widely with changes in the frequency of movement.2. At some frequency between 6 and 8 Hz, the reflex force tended to offset the non-reflex component of resistance, and thus to reduce the total resistance to movement. At this frequency the reflex response was particularly vigorous, with a deep modulation of electromyogram (e.m.g.) activity and a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 22 publications
(31 reference statements)
2
64
1
Order By: Relevance
“…One possible cause of this would be multiple EMG bursting on each stretch cycle, as has been reported previously (Andrews et al 1973b;Rack et al 1983), but examination of the raw data provided no evidence for multiple bursting here. The raw data in Figure 2b show a case where harmonics were strongly present, taken from the subject whose spectra are shown in Figure 5, at an amplitude of 1.9 o and frequency of 8.5 Hz.…”
Section: Discussionmentioning
confidence: 77%
“…One possible cause of this would be multiple EMG bursting on each stretch cycle, as has been reported previously (Andrews et al 1973b;Rack et al 1983), but examination of the raw data provided no evidence for multiple bursting here. The raw data in Figure 2b show a case where harmonics were strongly present, taken from the subject whose spectra are shown in Figure 5, at an amplitude of 1.9 o and frequency of 8.5 Hz.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, such interactions seem unlikely to produce the right kind of effect. Stretching at frequencies close to that of the 'spontaneous' firing of a motoneurone (or to its harmonics) should more readily phase-lock its firing onto the stimulus cycle, and so evoke an unduly deep modulation of the EMG; such an action is well known for spindle afferents, and might contribute to tremor (Goodwin, Hulliger & Matthews, 1975;Rack, Ross, Thilmann & Walters, 1983). Thus motoneurone rhythmicity seems more likely to create a peak than a trough in the frequency response at 20-25 Hz.…”
Section: Behaviour Of Single Motor Unitsmentioning
confidence: 99%
“…There is evidence that spindle afferent discharges are related to changes in the elastic properties of the tissues in which they are embedded 59 . Specifically, it has been reported that stiffer muscle-tendon elements ensure that the muscle spindles are more sensitive to imposed external forces 60 . Strength training has been shown to increase the stiffness not only of muscular but also of connective tissues surrounding the targeted joint 61,62 .…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…or "Where on the object would you like to hit a ball?" Whether the objects were tennis rackets (ranging in length from 53 to 73cm) or wooden rods (44,60, and 75cm) with attached metal rings (at 1/3 or 2/3L), perceived sweet spot (center of percussion) was distinguished from perceived length. Both rods and rackets showed the familiar 1/3 scaling of perceived length to I xx albeit with a lower intercept than was found for young participants 52 .…”
mentioning
confidence: 99%